Improvement of Gold Nanorods in Photothermal Therapy: Recent Progress and Perspective - Shengnan Liao; Wang Yue; Shuning Cai; Quan Tang; Weitong Lu; Lingxiao Huang; Tingting Qi; Tingting Qi; Jinfeng Liao (Frontiers Media S.A., 2021)
Cancer is a life-threatening disease, and there is a significant need for novel technologies to treat cancer with an effective outcome and low toxicity. Photothermal therapy (PTT) is a noninvasive therapeutic tool that transports nanomaterials into tumors, absorbing light energy and converting it into heat, thus killing tumor cells. Gold nanorods (GNRs) have attracted widespread attention in recent years due to their unique optical and electronic properties and potential applications in biological imaging, molecular detection, and drug delivery, especially in the PTT of cancer and other diseases. This review summarizes the recent progress in the synthesis methods and surface functionalization of GNRs for PTT. The current major synthetic methods of GNRs and recently improved measures to reduce toxicity, increase yield, and control particle size and shape are first introduced, followed by various surface functionalization approaches to construct a controlled drug release system, increase cell uptake, and improve pharmacokinetics and tumor-targeting effect, thus enhancing the photothermal effect of killing the tumor. Finally, a brief outlook for the future development of GNRs modification and functionalization in PTT is proposed.